2017
DOI: 10.1111/cxo.12528
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported optometric practise patterns in age‐related macular degeneration

Abstract: These results highlight the emergence of multimodal and advanced imaging (especially optical coherence tomography) in the assessment of age-related macular degeneration by optometrists. Clinically significant variations in self-rated test competency and the understanding regarding nutritional supplements for different stages of age-related macular degeneration suggest that further work to up-skill optometrists may be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
(50 reference statements)
2
13
0
Order By: Relevance
“…4 Several factors contribute to the difficulty and a lack of uniformity in AMD assessment. 5 The condition is phenotypically heterogeneous. Evaluation of clinical markers for determining AMD stage and risk of progression (drusen size, pigmentary abnormalities), using funduscopy and/or retinal photography, may also vary between clinicians.…”
mentioning
confidence: 99%
“…4 Several factors contribute to the difficulty and a lack of uniformity in AMD assessment. 5 The condition is phenotypically heterogeneous. Evaluation of clinical markers for determining AMD stage and risk of progression (drusen size, pigmentary abnormalities), using funduscopy and/or retinal photography, may also vary between clinicians.…”
mentioning
confidence: 99%
“…In the UK and internationally, there has been a shift towards integrating advanced imaging technologies, particularly OCT, into routine case finding 25–28. Global interest in the value of SD-OCT for detecting retinal disease has recently been fuelled further by the application of artificial intelligence (AI) based on deep learning algorithms 29 30.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, and internationally, there has been a shift towards integrating advanced imaging technologies, particularly optical coherence tomography (OCT), into routine optometric practice . However, it is not clear whether the incorporation of advanced imaging leads to an improved diagnostic performance.…”
Section: Introductionmentioning
confidence: 99%
“…7 In the UK, and internationally, there has been a shift towards integrating advanced imaging technologies, particularly optical coherence tomography (OCT), into routine optometric practice. [12][13][14][15] However, it is not clear whether the incorporation of advanced imaging leads to an improved diagnostic performance. A recent study in Australia using case vignettes found that the diagnostic accuracy of macular disease is only marginally improved with the incorporation of advanced imaging techniques compared to colour fundus photography alone; the additional information from advanced imaging led to increased numbers of false positives and a greater tendency to refer cases to secondary care.…”
Section: Introductionmentioning
confidence: 99%